(3GdSff GdcHQis - (3GdfSGFj , CMeO Hf Ydj Hf TYjH Hf Ydj Hf SfGf Hf HMQ Hf OjfGQ GdfSGFj, CHh YHO GdQMef,J (B303 (3g` s
(3ChdgG (B:s
(3bGd aj GdCUd GdefShN efgG gPg hgj aj fgGjI GdUMI eGdaXg GdLRA GdChd ef cJGH GdeMJi ef GdSff GdcHQi s
(3BNQgG (B:s
(3gPG BNQ GdKdK GdKGdK ef cJGH GdfSGFj aj GdMOK hgh BNQ cJGHg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B244s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1006s
Keywords: (3GdMOjK h GdeUWdMs